Did Medicaid expansion close African American-white health care disparities nationwide? A scoping review - Lonnie R. Snowden; Genevieve Graaf; Latocia Keyes; Katherine Kitchens; Amanda Ryan; Neal Wallace (BMC Public Health, 2022)
Abstract Objectives To investigate the impact of the Affordable Care Act’s (ACA) Medicaid expansion on African American-white disparities in health coverage, access to healthcare, receipt of treatment, and health outcomes. Design A search of research reports, following the PRISMA-ScR guidelines, identified twenty-six national studies investigating changes in health care disparities between African American and white non-disabled, non-elderly adults before and after ACA Medicaid expansion, comparing states that did and did not expand Medicaid. Analysis examined research design and findings. Results Whether Medicaid eligibility expansion reduced African American-white health coverage disparities remains an open question: Absolute disparities in coverage appear to have declined in expansion states, although exceptions have been reported. African American disparities in health access, treatment, or health outcomes showed little evidence of change for the general population. Conclusions Future research addressing key weaknesses in existing research may help to uncover sources of continuing disparities and clarify the impact of future Medicaid expansion on African American health care disparities.